P076: Do QR codes effectively engage patients in research while visiting the emergency department?. (May 2019) - Krebs, L.; Villa-Roel, C.; Ushko, D.; Sandhar, G.; Ruske, H.; Couperthwaite, S.; Holroyd, B.; Ospina, M.; Rowe, B.
Abstract : Introduction : Efforts to engage patients in research when presenting to emergency departments (EDs) have explored the utility of online tools; for example, through QR-based applications. It is unclear whether these are effective strategies for engaging patients in research activities while saving costs of in-person surveys. This study evaluated whether patients would participate in QR codes or short URL-linked surveys available in EDs across Alberta.Methods : A patient waiting room poster was developed as part of a stepped-wedge randomized controlled trial. The waiting room poster was introduced in 15 urban and regional Alberta EDs with a median annual volume of approximately 60, 000. A QR-code and short URL were placed on the poster inviting patients to participate in an online survey and evaluate the poster's usefulness and acceptability. Additionally, written discharge instructions, which were part of the intervention materials, were distributed with QR-code and short URL link to surveys for patients to share their ED care experience. Patients were not prompted by any staff or research personnel to encourage use of the QR codes or the short URLs; however, a survey was conducted with ED waiting room patients in 3 urban EDs to ascertain whether they had downloaded a QR reader on their devices and the frequency of use of these applications.Results : Given the stepped-wedge nature of the study, these materials were available for a total of approximately 123 months (3 sites for 13 months, 4 sites for 10 months, 4 sites for 7 months, and 4 sites for 4 months). Over the study period, 15 patients accessed and completed the online survey linked to the QR code or the short URL placed on the posters. No patients completed the online surveys linked to the QR code or the short URL placed on the discharge instructions. The in-person survey conducted within the ED waiting room identified that 34% of respondents had a QR code reader downloaded on their phone (108/316). Of those with a QR reader, 33% reported using the reader at least once within the last 6 months.Conclusion : In this study, few patients downloaded QR readers on their electronic devices while in the ED waiting room. Without prompting, this appears to be an ineffective strategy for engaging patients in emergency medicine research. Other engagement strategies optimizing human resource investment are urgently needed to effectively conduct research in EDs.